О малых колебаниях сжимаемой стратифицированной жидкости - Вронский, Б.М. (Український математичний журнал, 2006)
Вивчено характер спектра, повноту i базисність системи власних вeктopів. We study the structure of the spectrum and the completeness and basis property of a system of eigenvectors.